Combinatorial Discovery and Validation of Heptapeptides with UTP Binding Induced Structure. Issue 1 (28th July 2020) - Kroiss, Daniela; Aramini, James M.; Ragoonath, Sangitaa; Ulijn, Rein V.; Tuttle, Tell
Abstract: In biology, supramolecular recognition typically involves an 'induced‐fit' mechanism, where structures rearrange upon complexation to accommodate binding ligands. Designing minimalistic compounds with such adaptability is challenging as they involve subtle conformational changes that are energetically similar. Here, we demonstrate the integration of combinatorial screening with molecular modelling to identify heptapeptides that form a stable loop upon recognition of uridine triphosphate (UTP). Peptide sequences selected using phage display were refined computationally and correlated with experimental KD values. This combined approach may serve as a method for the de novo selection and subsequent rationalization of the compositional and organizational principles that dictate chemical functionality in flexible structures with dynamic conformations. Abstract : A good combination : We demonstrate integrated experimental screening with computational refinement to enable unbiased searching of the peptide sequence space for specific functions. This approach allows for the discovery of short peptides that undergo conformational adaption upon complexation with a single nucleotide (UTP), a feature that is ubiquitous in nature, but cannot be achieved through rational design.